1991
DOI: 10.1177/030089169107700512
|View full text |Cite
|
Sign up to set email alerts
|

Distant Metastases in Differentiated Thyroid Cancer: Long-term Results of Radioiodine Treatment and Statistical Analysis of Prognostic Factors in 214 Patients

Abstract: Long-term results and statistical analysis of prognostic factors in a series of 214 patients with distant metastases from differentiated thyroid cancer (DTC) are reported here. These 214 were part of a total series of 1457 patients with DTC referred to our center from 1967 to 1987. All patients underwent surgery and 131-I therapy and were treated with TSH suppressive doses of thyroid hormones. After a mean follow-up of 7.3 years including clinical, scintigraphic, radiological and laboratory investigations, 24.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 12 publications
4
43
1
Order By: Relevance
“…Multisite metastasis is generally considered to be associated with decreased survival, and limited extent of metastatic disease is a favorable factor for survival [7,15], although Pittas et al reported that the survival in patients who had a single bone lesion was not better than in those with multiple bone lesions [14]. Age is considered as a prognostic factor of improved survival [24,25], but in our study, age at diagnosis of bone metastasis was not statistically significant, maybe due to the small number of patients less than 45 years old (not described in above results). Early detection could initiate prompt therapy and improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…Multisite metastasis is generally considered to be associated with decreased survival, and limited extent of metastatic disease is a favorable factor for survival [7,15], although Pittas et al reported that the survival in patients who had a single bone lesion was not better than in those with multiple bone lesions [14]. Age is considered as a prognostic factor of improved survival [24,25], but in our study, age at diagnosis of bone metastasis was not statistically significant, maybe due to the small number of patients less than 45 years old (not described in above results). Early detection could initiate prompt therapy and improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…The levels above and below the vertebrectomy site were counted as parts of the anterior column construct when plating, Steinmann pins, or chest tube insertion were involved. Fourteen patients did not require posterolateral stabilization; of those who did, the median length of the construct was 6 vertebral levels (range [3][4][5][6][7][8][9][10][11][12][13][14]. Two patients underwent lumbopelvic or lumbosacropelvic fixation; in these instances, the sacrum or pelvis was treated as 1 level.…”
Section: Operative Datamentioning
confidence: 99%
“…15,24,26 Prior studies have assessed the prognostic factors associated with systemic metastasis from thyroid carcinoma; however, none have specifically investigated the factors that affect survival in patients undergoing surgery for spinal metastases. 3,5,13,16,18,21,25,32,36,39,40 Therefore, the objective of this study was to analyze a series of consecutive patients who underwent surgery for spinal metastasis from thyroid cancer in order to identify factors associated with postoperative survival and complications. This prognostic information may aid in clinical decision making, as patients with a more favorable prognosis may warrant more aggressive intervention and patients with poor life expectancy may be spared from aggressive surgery.…”
mentioning
confidence: 99%
“…Distant metastases are an uncommon event in DTC and a wide range in prevalence (4-23%) has been reported (1,2,3,4,5,6). Lungs are the most frequent site of distant metastasis in DTC and the resulting respiratory failure may be the most common cause of death.…”
Section: Introductionmentioning
confidence: 99%